A comparative study on the behavior of Riemann-Liouville and Caputo fractional derivatives of some functions - Inbaig, Abdlgader M.; Bashon, Yasmina M. (Libyan Journal of Science &Technology, 2025)
This paper presents an overview of fractional order derivative operators. Particular attention is devoted to the Riemann-Liouville and Caputo fractional derivative operators. A comparative study of these two frameworks to show how they behave geometrically. The computation results of some elementary function derivatives of fractional order are shown in graphic form and tabular for this purpose. The conclusion will include a few observations about derivatives of integer and fr Abdlgader M. Inbaig, Yasmina M. Bashon actional order.